2020
DOI: 10.3390/pharmaceutics12040355
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Microcontainers Improve In Situ Colonic Mucoadhesion and Absorption of Amoxicillin in Rats

Abstract: An increased interest in colonic drug delivery has led to a higher focus on the design of delivery devices targeting this part of the gastrointestinal tract. Microcontainers have previously facilitated an increase in oral bioavailability of drugs. The surface texture and shape of microcontainers have proven to influence the mucoadhesion ex vivo. In the present work, these findings were further investigated using an in situ closed-loop perfusion technique in the rat colon, which allowed for simultaneous evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…polymeric devices for oral drug delivery, are designed and fabricated as a reservoir with an opening on one side, to hold and carry a compound to the target site of release 15,16 . Previous studies have shown that microcontainers can facilitate protection of loaded contents through the various local environments of the GI tract 17,18 , controlled release of pharmaceuticals 19,20 and their tunable properties can increase the intestinal retention of a drug formulation 21,22 . After fabrication, the microcontainers are loaded with a compound followed by sealing with a polymeric lid 23 .…”
Section: Introductionmentioning
confidence: 99%
“…polymeric devices for oral drug delivery, are designed and fabricated as a reservoir with an opening on one side, to hold and carry a compound to the target site of release 15,16 . Previous studies have shown that microcontainers can facilitate protection of loaded contents through the various local environments of the GI tract 17,18 , controlled release of pharmaceuticals 19,20 and their tunable properties can increase the intestinal retention of a drug formulation 21,22 . After fabrication, the microcontainers are loaded with a compound followed by sealing with a polymeric lid 23 .…”
Section: Introductionmentioning
confidence: 99%
“…They have a cavity for drug loading on the top side, and since only one side is open, they can provide unidirectional drug release through the GI tract to increase drug absorption efficiency. The transit mechanism has been investigated using an ex vivo intestinal perfusion model and animal studies [7] , [21] . However, the mucoadhesion force of a single MC has not been thoroughly studied because of the limited resolution of the conventional texture analyzer.…”
Section: Validation and Characterizationmentioning
confidence: 99%
“…The conventional punching or blanking process includes three basic steps illustrated in Figure 1A: (1) A metal sheet is positioned on an inflexible die. (2) The punch and the metal sheet are brought into contact by the application of a high force. The penetration of the punch into the voids of the die results in build-up of stresses in the metal sheet with the maximum stress located at the edges of the punch.…”
Section: Micromechanical Punching (Mmp)mentioning
confidence: 99%
“…In order to influence the biodistribution of drug-loaded micro- and nanoparticles in pharmaceutics and the targeting, release profile, and bioavailability of the drug, the ability to precisely manipulate size, shape, and surface properties of the particles is important [ 1 , 2 ]. Similarly, the composition, size and shape of a metallic nanoparticle dictate the resonant frequency of the electron oscillation in localized surface plasmonics.…”
Section: Introductionmentioning
confidence: 99%